Emotions and Affective Polarization: How Enthusiasm and Anxiety About Presidential Candidates Affect Interparty Attitudes. Issue 2 (March 2020) - McLaughlin, Bryan; Holland, Derrick; Thompson, Bailey A.; Koenig, Abby
In the context of an increasingly divided populace, this article considered how the emotions (enthusiasm and anxiety) partisans feel toward U.S. presidential candidates may heighten or diminish affective polarization. In Study 1 (American National Election Studies [ANES] 2008–2009 panel data), we found that enthusiasm for the in-group candidate and anxiety about the out-group candidate were related to higher levels of affective polarization, whereas enthusiasm for the out-group candidate was related to lower levels of affective polarization. In Study 2 (2016 panel data), we found that in-group enthusiasm was related to higher levels of affective polarization and out-group enthusiasm was related to lower levels of affective polarization, but neither in-group nor out-group anxiety was significantly related to affective polarization. These findings highlight that enthusiasm about out-group candidates may have a unique ability to disrupt affective polarization and that it is important to consider the source of an emotion response, not just the type of emotion.